Environmental management and firm performance on firm value moderated by good corporate governance - Anggawikara, Sherly; Budidarma, I Gusti Agung Musa (International Journal Labs, 2023)
This research aims to analyze the influence of environmental management and firm performance on firm value, which is moderated by good corporate governance, which is proxied by board size and independent commissioners. The research design is quantitative research with the title